A 526 mJ Subnanosecond Pulsed Hybrid-Pumped Nd：YAG Laser - 石江鹏 辛建国 刘军 陈家斌 Sher Zaman (Chinese physics letters, 2017)
A hybrid-pumped Nd：YAG pulse laser with a double-pass two-rod configuration is presented. The focal length of offset lens is particularly studied to compensate for the thermal lens effect and depolarization. For input pulse energy of 141 μJ with pulse duration of 754ps, the pulse laser system delivers 526mJ pulse energy and 728ps pulse width output at lO Hz with pulse profile shape preservation. The energy stability of the laser pulse is less than 3%, and the beam quality factor M2 is less than 2.26.